Article Commentary: Environmental Health: Threats and their Interactions - Douglas Holdstock (SAGE Publishing, 2008)
Improvements in the provision of an acceptable standard of health care, particularly in the developing world, will be undermined by three ongoing processes: ongoing armed conflicts; the threat of global warming due to rising levels of greenhouse gases, particularly carbon dioxide emitted by developed countries; and by rapidly rising populations. The key features of these three threats are summarised, and it is shown that interactions between them increase both the likelihood of their occurrence and the probable harm that they will cause. Some of the interactions are described, with ways of providing health care taking into account the threats and their interactions, and the paradox is emphasised that better health care in the developing world will further increase population growth followed by increased greenhouse gas emissions. Improved education for women and free and unlimited access to modern methods of contraception are vital.